(untitled) (gjstudies, 2021)
This research paper investigates the profound and persistent challenges inherent in themeasurement and financial reporting of intellectual capital (IC) assets within contemporaryorganizational frameworks. Moving beyond conventional critiques of existing accountingstandards, this study introduces a novel, tripartite methodological framework that synthesizes principles from hermeneutic phenomenology, complex adaptive systems theory, andagent-based modeling to reconceptualize IC not as a static, discrete asset, but as a dynamic, emergent property of organizational networks. The central research question interrogates whether the fundamental epistemic assumptions of double-entry bookkeeping areontologically compatible with the fluid, contextual, and non-linear nature of knowledgebased value creation. Through a qualitative meta-analysis of reporting practices in 45knowledge-intensive firms and the development of a proof-of-concept simulation model, wedemonstrate that traditional historical cost and fair value accounting paradigms systematically misrepresent IC, leading to significant information asymmetry and valuation gaps. Ourfindings reveal that the primary challenge is not merely technical or standard-setting, butphilosophical, residing in the incommensurability between the reductionist logic of financialquantification and the holistic, relational essence of intellectual capital. The paper concludesby proposing the contours of a ’narrative-networked’ supplementary reporting model thatemphasizes qualitative disclosures of knowledge flows, innovation ecosystems, and relationalcapital maps, arguing for a paradigm shift from measurement to meaningful representation.This contribution is original in its cross-disciplinary theoretical foundation and its rejectionof incremental adjustment to existing standards in favor of a more radical re-imagination ofvalue reporting in the intangible economy